Legislative Performance of the Sangguniang Panlungsod of Sorsogon City in Disaster Risk Reduction Management - Jovelle L. Duana; Carl Dominic D. Celestial (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study evaluates the legislative and official decisions made by the Sangguniang Panglungsod of Sorsogon City regarding disaster management from 2022 and 2024. The research groups these legislations into the four phases of disaster management: Prevention and Mitigation, Preparedness, Response, and Rehabilitation and Recovery. By categorizing these legislations, the study indicates how these help the city to be resilient and emphasize areas which improvements in these policies are needed. A qualitative design was used, applying document and thematic analysis to review official city records. Findings indicates that the city government has made consistent progress in fund, resource allocation, and disaster risk management planning. However, the analysis indicates a lack of proper post evaluation. The study suggests that the Sangguniang Panglungsod should utilize a monitoring tool to bridge the gap on policy enactment and ground level enforcement of DRRM policies.